Mass and heat transfer in turbulent bed contractor by Fares T. Abdul-Hamid. - Abdul-Hamid, Fares T. (1979)
The coefficient of mass and heat transfer have been measured in a turbulent bed contactor. The turbulent bed contactor is a cylindrical column containing a low density solid spheres which are fluidized by upward flowing gas and irrigated by downward flowing liquid. Atmospheric air is used as the gas while hot water is used as the liquid.
Values of the mass and heat transfer coefficients in the gas phase are reported as a function of the air superficial velocity, water flow rate and the static bed height. These values show that the transfer coefficients increases with the corresponding increase of the air velocity and the water flow rate. The values also show that the transfer coefficients increased rapidly as the static bed height increases up to a certain bed height which is the effective bed height. Beyond the effective bed height, the transfer coefficients are almost constant.
Values of the minimum fluidizing velocity are given as a function of the liquid flow rates. These values showed that the minimum fluidizing velocity decreases as the water flow rate increases. These values are much lower than the predicted minimum fluidizing velocity of the dry particles.
Thesis (M.S. Chemical Engineering) --University of the Philippines, Diliman.
Keywords: Heat -- Transmission; Mass transfer